Kontestasi Budaya Barat dan Dampaknya terhadap Perempuan: Analisis dari Perspektif Viktimologi - Maulana Khidlir (Sekolah Tinggi Agama Islam Taruna Surabaya, 2025)
Victimology is the study of victims in various contexts, such as crime, accidents, and natural disasters. Initially focused on crime victims, the field has evolved to encompass a wide range of human suffering. Women are often a central focus in victimology due to their increased vulnerability to crime caused by social and cultural factors, especially patriarchal cultures. Cultural contestation, particularly influenced by Western culture, significantly impacts women globally. This study examines the effects of cultural contestation on women, including physical and psychological violence, social stigma, and marginalization. Furthermore, victimology plays a crucial role in designing recovery and intervention strategies to support female crime victims, with an emphasis on psychological recovery, social reintegration, and access to justice. The victimological approach leads to the development of more inclusive and responsive support programs and restorative justice as an alternative for restoring relationships among victims, perpetrators, and society.